2023
DOI: 10.3390/plants12020401
|View full text |Cite
|
Sign up to set email alerts
|

Protein Changes in Shade and Sun Haberlea rhodopensis Leaves during Dehydration at Optimal and Low Temperatures

Abstract: Haberlea rhodopensis is a unique resurrection plant of high phenotypic plasticity, colonizing both shady habitats and sun-exposed rock clefts. H. rhodopensis also survives freezing winter temperatures in temperate climates. Although survival in conditions of desiccation and survival in conditions of frost share high morphological and physiological similarities, proteomic changes lying behind these mechanisms are hardly studied. Thus, we aimed to reveal ecotype-level and temperature-dependent variations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…In fact, similar proteome changes in roots and fronds during dehydration and rehydration are observed. A significant number of proteins that appear during desiccation in leaves correspond to the alterations in carbohydrate metabolism [58]. These alterations contribute to the removal of the starch granules from chloroplasts and the accumulation of carbohydrates in the secondary vacuoles [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, similar proteome changes in roots and fronds during dehydration and rehydration are observed. A significant number of proteins that appear during desiccation in leaves correspond to the alterations in carbohydrate metabolism [58]. These alterations contribute to the removal of the starch granules from chloroplasts and the accumulation of carbohydrates in the secondary vacuoles [59].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, shotgun proteomics showed the enhanced protein abundance of dehydrins, ELIPs, and HSPs in leaves of H. rhodopensis during desiccation [61]. The increased protein content of dehydrins was monitored during drought-and freezing-induced desiccation of Balkan's resurrection species H. rhodopensis, Ramonda serbica, and Ramonda nathaliae [58,62]. Dehydrins have chaperone-like functions in plant cells related to the protection of proteins and membrane stabilization during stress, but they also act as ROS scavengers [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Van Buren et al [44] proposed that duplication of ELIP genes in the genomes of resurrection plants is related to the evolution of desiccation tolerance and the protection of chloroplasts from photooxidative damage. ELIP transcripts and proteins are highly expressed in the leaves of H. rhodopensis in response to desiccation and during the early hours after rehydration [10,39,41,[45][46][47]. Recently, we found that rehydration after freezinginduced desiccation enhanced the ELIP transcript abundance more strongly in leaves compared with rehydration after drought [41].…”
Section: The Role Of Protective Proteins For Acquisition Of Freezing ...mentioning
confidence: 99%
“…As could be expected, most of them live under desert or semi-desert conditions. However, there are also species that belong in humid tropical regions in Africa and South America or survive winters with freezing temperatures in Europe [3][4][5][6][7][8][9][10][11]. Their strategies to withstand desiccation are predetermined, constitutive (e.g., in-advance high-abundance of protective compounds, including metabolites), and/or inducible, leading to reprogramming at the transcriptome and metabolome levels upon stress establishment [4,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%